Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1155/2013/205082
|View full text |Cite
|
Sign up to set email alerts
|

Zeaxanthin Induces Apoptosis in Human Uveal Melanoma Cells through Bcl-2 Family Proteins and Intrinsic Apoptosis Pathway

Abstract: The cytotoxic effects of zeaxanthin on two human uveal melanoma cell lines (SP6.5 and C918) and related signaling pathways were studied and compared to effects on normal ocular cells (uveal melanocytes, retinal pigment epithelial cells, and scleral fibroblasts). MTT assay revealed that zeaxanthin reduced the cell viability of melanoma cells in a dose-dependent manner (10, 30, and 100 μM), with IC50 at 40.8 and 28.7 μM in SP6.5 and C918 cell lines, respectively. Zeaxanthin did not affect the viability of normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 49 publications
(48 reference statements)
2
32
0
Order By: Relevance
“…The mitochondrial pathway is regulated by the Bcl-2 family proteins which includes the anti-apoptotic proteins (Bcl-2, etc. ), the proapoptotic proteins (Bax and Bak) (Bi et al, 2013). Accumulation of proapoptotic proteins on the mitochondrial outer membrane results in increased mitochondrial membrane permeability, causing the release of cyt c into the cytoplasm (Strasser et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial pathway is regulated by the Bcl-2 family proteins which includes the anti-apoptotic proteins (Bcl-2, etc. ), the proapoptotic proteins (Bax and Bak) (Bi et al, 2013). Accumulation of proapoptotic proteins on the mitochondrial outer membrane results in increased mitochondrial membrane permeability, causing the release of cyt c into the cytoplasm (Strasser et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition, it is reported that D-GalN/LPS induced MAPK activation in mice. 7 Thymoquinone (TQ), a bioactive natural product obtained from the black cumin seeds of Nigella sativa Linn, is a widely used spice or herb throughout India and the Middle East. 6 Apoptosis can be induced through extrinsic pathway followed by caspase-8 activation and via the mitochondrial pathway by triggering the Bcl-2 family.…”
Section: Introductionmentioning
confidence: 99%
“…Zeaxanthin did not affect the viability of normal ocular cells even at the highest levels tested (300 μM), suggesting that zeaxanthin has a selectively cytotoxic effect on melanoma cells; in addition, zeaxanthin (30 μM) induced apoptosis in melanoma cells [28].…”
Section: Discussionmentioning
confidence: 88%
“…Lutein and zeaxanthin, naturally occurring carotenoids, have shown to reduce the risk of cataracts and age-related macular degeneration [27]. Zeaxanthin is related with the reduction of melanoma cells viability [28]. Lutein caused significant DNA damage in human retinal pigment epithelial cells [29].…”
Section: Introductionmentioning
confidence: 99%